Are Japanese spousal terms as gender-biased as they seem? An examination using implicit association measures - Ri Nin; Kazuo Mori (PLoS ONE, 2026)
This study investigated whether traditional Japanese spousal terms— shujin (“master”) and kanai (“inside-the-house”)—retain male-dominant associations at an implicit level. Using a paper-based Implicit Association Test (the FUMIE Test), we compared implicit attitudes toward traditional and neutral spousal terms among Japanese university students. The results showed no significant difference between the two term pairs, suggesting that shujin and kanai may have become conventionalized rather than continuing to evoke their hierarchical literal meanings. However, a significant gender difference emerged: male participants evaluated male-associated terms more positively, whereas female participants showed no such bias. These findings indicate that while traditional terms may no longer strongly activate hierarchical associations at an implicit level, latent gender asymmetries persist, particularly among men. The study highlights the importance of examining implicit dimensions of language use and provides a useful methodological tool for investigating gender bias in sociolinguistic research.